Have your baby and get out. We need this bed for somebody else. Compassionate intrapartum communication : a discourse analysis of language use during labour in South African public and private maternity settings - Minnaar, Sulette (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.